Encountering “the Other” in Religious Social Media: A Cross-Cultural Analysis - Shoaib Ul Haq; Ray Yiu-keung Kwok (Social Media + Society)
This study examines how social media platforms shape encounters with religious “others” across diverse cultural contexts, focusing on Muslim users in Pakistan and Buddhist/Christian users in Hong Kong. Through qualitative interviews and reflexive thematic analysis, we identify key patterns in how these platforms both facilitate and constrain meaningful interreligious dialogue. We find that while religious social media can expand exposure to diverse perspectives, it often reinforces in-group boundaries and amplifies polarization through echo chamber effects. Our findings further reveal that users engage in selective exposure, primarily interacting with like-minded believers, while also developing new competencies as “religious bridge-builders” in some cases who cultivate new competencies for interreligious communication. We develop a theoretical framework of “digital othering” to explain how believers navigate religious identity, knowledge, and community in online spaces. By adopting a cross-cultural comparative approach, the study contributes to our understanding of religion in the digital age, offering insights into the culturally specific manifestations of digital othering while also identifying broader patterns that transcend particular contexts. This research advances the field of digital religion studies, providing a nuanced understanding of how social media reshapes religious expression, authority, and interreligious relations in an increasingly digitized global society.